A cAMP/CRP-controlled mechanism for the incorporation of extracellular ADP-glucose in Escherichia coli involving NupC and NupG nucleoside transporters. Issue 1 (December 2018) - Almagro, Goizeder; Viale, Alejandro; Montero, Manuel; Muñoz, Francisco; Baroja-Fernández, Edurne; Mori, Hirotada; Pozueta-Romero, Javier
Abstract ADP-glucose is the precursor of glycogen biosynthesis in bacteria, and a compound abundant in the starchy plant organs ingested by many mammals. Here we show that the enteric speciesEscherichia coli is capable of scavenging exogenous ADP-glucose for use as a glycosyl donor in glycogen biosynthesis and feed the adenine nucleotide pool. To unravel the molecular mechanisms involved in this process, we screened theE .coli single-gene deletion mutants of the Keio collection for glycogen content in ADP-glucose-containing culture medium. In comparison to wild-type (WT) cells, individual∆nupC and∆nupG mutants lacking the cAMP/CRP responsive inner-membrane nucleoside transporters NupC and NupG displayed reduced glycogen contents and slow ADP-glucose incorporation. In concordance, ∆cya and∆crp mutants accumulated low levels of glycogen and slowly incorporated ADP-glucose. Two-thirds of the glycogen-excess mutants identified during screening lacked functions that underlie envelope biogenesis and integrity, including the RpoE specific RseA anti-sigma factor. These mutants exhibited higher ADP-glucose uptake than WT cells. The incorporation of either∆crp, ∆nupG or∆nupC null alleles sharply reduced the ADP-glucose incorporation and glycogen content initially witnessed in∆rseA cells. Overall, the data showed thatE .coli incorporates extracellular ADP-glucose through a cAMP/CRP-regulated process involving the NupC and NupG nucleoside transporters that is facilitated under envelope stress conditions.